Sulfonylureas the presente state in the treatment of diabetes Mellitus type 2 - Pando-Alvarez, Rosa María (2020)
A current review of sulfonylureas as oral hypoglycemic agent in the treatment of diabetes mellitus type 2, particularly of the second and third generation sulfonylureas is performed. It is also reviewed its mechanism of action, cardiovascular risk, their adverse effects, the recommendation according to the ADA, AACE and ALAD guidelines and its use in patients infected with COVID-19.